2011
DOI: 10.1017/s1751731111000231
|View full text |Cite
|
Sign up to set email alerts
|

Oral and intranasal administration of somatostatin DNA vaccine mediated by attenuated Salmonella Enterica Serovar Typhimurium to promote growth of piglets

Abstract: An attenuated strain of Salmonella typhimurium has been used as a carrier for oral and intranasal genetic immunization. Here, we evaluate the efficacy of a vaccine strain of S. typhimurium. CSO22 (pGM-CSF/SS, plasmid granulocyte-macrophage colonystimulating factor/somatostatin) expressing two copies of SS genes. A total of 115 piglets, aged 2 months old, were either orally or intranasally immunized against the vaccine strain CSO22 (pGM-CSF/SS) with three dosages (5 3 10 10 colony forming units (CFU), 5 3 10 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Liu et al . have also found that weight gain by piglets was only in the high‐dose orally immunized group against the SS DNA vaccine CSO22 (pGM‐CSF/SS) significantly higher compared to the control group at week 4 after primary immunization ( P < 0.05). The increase in growth rate in the high‐dose orally immunized group was also decreased at week 8 (20.86%) compared with week 4 (10.26%) after primary immunization.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Liu et al . have also found that weight gain by piglets was only in the high‐dose orally immunized group against the SS DNA vaccine CSO22 (pGM‐CSF/SS) significantly higher compared to the control group at week 4 after primary immunization ( P < 0.05). The increase in growth rate in the high‐dose orally immunized group was also decreased at week 8 (20.86%) compared with week 4 (10.26%) after primary immunization.…”
Section: Discussionmentioning
confidence: 89%
“…Attenuated Salmonella was selected as an attractive delivery vector of heterologous antigens for oral immunization that could elicit systemic and mucosal immune responses . In previous studies, the oral SS DNA vaccine CSO22 (pGM‐CSF/SS) delivered by attenuated Salmonella typhimurium successfully induced antibody responses against SS and enhanced the growth of immunized mice and piglets . However, there was an antibiotic resistance gene in the CSO22 (pGM‐CSF/SS) that may cause antibiotic resistance and environmental problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant Salmonella have been used as vaccine vectors to deliver both DNA and protein vaccines from a wide variety of bacterial, viral and parasitic sources [16,17]. Attenuation virulence bacteria, which can penetrate host cells delivering vaccine antigen to APCs, can be used effectively to transport immunogens [18,19]. …”
Section: Introductionmentioning
confidence: 99%